Persuasive Strategies in Selected UNICEF Speaker’s Speech - Oktiani, Yufita Ria; Putri, Evi Jovita (Bina Nusantara University, 2022)
The research examined the persuasive strategies employed in selected UNICEF speakers’ speeches (BTS - RM and Jin, Millie Bobby Brown, and David Beckham). The observation aimed to determine the types of persuasive strategies used in selected UNICEF speakers’ speeches and how they were implemented. The research employed a descriptive qualitative approach in its research design. In the data analysis process, the analysis was conducted by describing and interpreting each data point in the form of words or utterances according to the context. A purposive sampling of all facts was used to collect data. In addition, the research used Aristotle’s theory of persuasion as a reference to help understand and analyze the data found from the speech. According to the data analysis, the research discovers 49 data points that utilize persuasive strategies. They employ all of Aristotle’s persuasive strategies to persuade their audience. These are the strategies of ethos, pathos, and logos. In their speeches at the children’s day event, BTS, and David mostly express pathos, while Millie mostly expresses logos. It proves that by expressing their credibility, serving realistic information, and including the hearer’s emotions in their speech, UNICEF speakers intentionally attempt to achieve their purpose.